Neutral helium line profiles through the simulation of local interactions. Issue Volume 15:Issue S357(2019) (October 2019) - Tremblay, Patrick; Beauchamp, Alain; Bergeron, Pierre
Abstract: For the past 25 years, we have been considering the Stark effect for neutral helium lines in DB white dwarfs using the standard Stark broadening theory in both the impact regime (in the center of the lines) and the quasi-static regime (in the wings) for the electrons, while neglecting the effect of ions in motion. Although this is probably a good approximation based on previous theoretical work, the transition between the two regimes for the electrons and the contribution of the ions very near the core might be poorly represented. To better represent these particularities, we report here the results of a new series of simulations that treat the local dynamics and interactions of both electrons and ions around a neutral helium atom. From these simulations, we produce new improved line profiles, which we compare with our previous analytical results.